Disentangling the molecular mechanisms of disease suppression by endophytic Flavobacterium sp. 98 - Pan, Xinya; Elsayed, Somayah S.; van Wezel, Gilles P.; Raaijmakers, Jos M.; Carrión, Víctor J. (Elsevier, 2025)
Endophytic microorganisms colonize internal plant tissues and enhance host resistance to pathogens. We previously showed that endophytic Flavobacterium sp. 98 (Fl98) protects sugar beet against the fungal root pathogen Rhizoctonia solani via biosynthetic gene cluster 298 (BGC298). However, the molecular mechanisms underlying this protection remained poorly understood. Here, comparative metabolomic analyses revealed that knockout of BGC298 led to reduced production of the antifungal compound 5,6-dimethylbenzimidazole (DMB) in Fl98. Wehypothesized that BGC298 is involved in regulating DMB biosynthesis and therefore contributes to Fl98’s disease suppression as a novel protective mechanism. Subsequent site-directed mutagenesis of the DMB-synthase gene bluB abolished DMB production by Fl98, and both ΔBGC298 and ΔbluB mutants were compromised in protecting sugar beet seedlings in greenhouse bioassays. Bioinformatic analyses further indicated that bluB is widespread across Flavobacterium, while BGC298 is limited to a small subset of plant-associated strains. Together, our findings highlight the pivotal role of BGC298 and DMB biosynthesis in plant protection by endophytic Flavobacterium sp. 98
Keywords: Flavobacterium; Suelos supresivos; Microbioma endofítico; Benzimidazoles; Genómica; Flavobacterium; Disease-suppressive soil; Endophytic microbiome; 5,6-dimethylbenzimidazole Molecular mechanisms; Comparative genomics